DISEASE-ASSOCIATED SYSTEMIC COMPLICATIONS IN CHILDHOOD NEPHROTIC SYNDROME: A SYSTEMATIC REVIEW - Al Ansoriani, Marogi; Rahayu Kosasih, Dina Mentayani; Alam Al Ansoriani, Nuansa Nur (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Nephrotic syndrome (NS) is characterized by massive proteinuria (more than 40 per hour) which causes hypoalbuminemia (less than 30), hyperlipidemia, edema, and various other complications. This is caused by increased permeability due to damage to the basement membrane of the glomerulus of the kidney. The aim: This study aims to show about Disease-Associated Systemic Complications in Childhood Nephrotic Syndrome. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 74 articles, whereas the results of our search on SagePub brought up 351 articles. The results of the search conducted for the last year of 2013 yielded a total 71 articles for PubMed and 202 articles for SagePub. The result from title screening, a total 22 articles for PubMed and 38 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Nephrotic syndrome is one of the most common kidney diseases in children. Patients with nephrotic syndrome experience protein loss that has a negative impact on various biological functions and can result in disease-related complications.